An Enhanced Ocean Acidification Observing Network: From People to Technology to Data Synthesis and Information Exchange - Tilbrook, Bronte; Jewett, Elizabeth B.; DeGrandpre, Michael D.; Hernandez-Ayon, Jose Martin; Feely, Richard A.; Gledhill, Dwight K.; Hansson, Lina; Isensee, Kirsten; Kurz, Meredith L.; Newton, Janet A.; Siedlecki, Samantha A.; Chai, Fei; et al. (Frontiers in Marine Science, 2019)
A successful integrated ocean acidification (OA) observing network must include 1) scientists and technicians from a range of disciplines (from physics to chemistry to biology to technology development) and across the globe; 2) government, private, and intergovernmental support; 3) regional cohorts working together on regionally specific issues; 4) publicly accessible data from the open ocean to coastal to estuarine systems; 5) close integration with other networks focusing on related measurements or issues including the social and economic consequences of OA; and 6) observation-based informational products useful for decision making such as management of fisheries and aquaculture. The Global Ocean Acidification Observing Network (GOA-ON), a key player in this vision, seeks to expand and enhance geographic extent and availability of coastal and open ocean observing data to ultimately inform adaptive measures and policy action, especially in support of the United Nations 2030 Agenda for Sustainable Development. GOA-ON works to empower and support regional collaborative networks such as the Latin American Ocean Acidification Network, supports new scientists entering the field with training, mentorship, and equipment, refines approaches for tracking biological impacts, and stimulates development of lower-cost methodology and technologies allowing for wider participation of scientists. GOA-ON seeks to collaborate with and complement work done by other observing networks such as those focused on carbon flux into the ocean, tracking of carbon and oxygen in the ocean, observing biological diversity, and determining short- and long-term variability in these and other ocean parameters through space and time.